O desassossego da permanência pós-moderna: subjetividade, cenas midiáticas e cultura do consumo - Gheirart, Oziel (2009)
The digital project has been implemented in the Post-Modernity as something discontinuously decisive. With the help of the mediatic polyphony, which promotes this transposition to the imateriality, the subject disconnect to invisible fields. The reality is violently altered by virtuality. Life becomes eternal and present through new spacial categories, time and speed. The old model of the subject shatters when it is confronted to a new mobile culture, which starts getting a form. The experience is brutally altered in its re-enchantment, in the process of estheticizing life, in the inverted logic of consume and is reflected in the constitution of culture. The latter needs new forms to inteerpret the new reality. Thus, the concretion of exteriority and of the ephemeral become autonomous in a still misty horizon. In a world whose mark is the ephemeral, how can one still think of an individual who can still feel enchantment for society? How can the perspective of the human being as a transforming-agent be possible in a society dominated by individualism, the lack of social compromise and even eye-to-eye contact among people? The routine of our "modern times" has been devoured by the technological voracity and by the ferocity of capital. Those seem to divide and make any chance of re-grouping, of fellowship, of "alive and kicking" humanity, of utopia. Thus, what intertwines the actions is an uncanny feeling, a unquietness. How can the subject be thought amongst that all? Such reflexions have emerged in this work, which aims to not only a diagnostic of our present situation - a world in which so many technological communication resources make us go beyond our real condition to escape from our own reality - but also to new possibilities.